Strengthening Community Economic Independence Through Malaysia Sharia Microfinance Institutions - As’ad; Rosmanidar, Elyanti; Kusnadi, Dedek; Fusfita, Nurlia; Rahma, Sri; Ramadhani, Febi; Kunnuzi; Delvianti, Sintia; Al Hawari, Rifqy Habibi (IJCS: International Journal of Community Service, 2022)
This research aims to investigate the role of sharia microfinance institutions in strengthening the economic independence of communities in Malaysia. The main focus of this research is to analyze the contribution of sharia microfinance institutions in increasing financial access for society, especially in the context of sharia economics. The research method used is descriptive analysis by collecting primary data through interviews and secondary data from related literature. It is hoped that the findings from this research will provide in-depth insight into how sharia microfinance institutions can be an effective instrument in building the economic independence of communities in Malaysia, as well as provide relevant policy recommendations to support the development of the sharia economic sector more broadly